Diasporas, Cultures of Mobilities, 'Race' 1 Diasporas and Cultures of Migrations - Misrahi-Barak, Judith; Raynaud, Claudine (Horizons anglophones, 2014)
This volume examines the evolution of the concept of diaspora since the advent of Diaspora Studies in the 90s, specifically vis-à-vis other concepts: transnationalism, cosmopolitanism, creolization. The essays depict the discontinuities of diasporic experience, but also its ongoing negotiations. Building on transatlantic, gender studies and queer theory, they address the theoretical turn when sexual difference is taken into account and gender troubled. Allying theory and case studies, covering diasporas as diverse as the African, Caribbean, Palestinian, South and South-East Asian diasporas, the dispersion of Romas, the spaces of the Indian Ocean, South Africa and New Zealand, this volume promotes another diasporic model: multidirectional, plural and global. It finds in literature and film tools to think the 'super-diversity' and the contradictions of our global world.